Rethinking the role of law in adapting to climate change. (1st July 2021) - McDonald, Jan; McCormack, Phillipa C.
Abstract: The article evaluates the role of law in adaptation over the past decade. We track the emergence of international adaptation law within the climate and non‐climate regime, alongside increasingly dire extreme events and strident scientific consensus. Examining the growth in national and subnational laws for adaptation, we reflect on the role of framework legislation and legal mechanisms used in sectoral laws. Based on progress over the past decade, we outline how the role of law can be enhanced and accelerated in the decade ahead. We identify important trends in adaptation law and consider the potential for these innovations to drive future adaptation: the sheer growth in priority and volume of laws directed towards adaptation; the intersection of adaptation with other policy domains, especially disaster risk reduction; the need for improved architecture for funding adaptation; and the important role of strategic litigation. Largely absent from the past decade of adaptation law reform is evaluation of effectiveness, or examples of systemic reform that addresses underlying causes of vulnerability. With slow progress in implementing transformational adaptation law reform, we identify five design principles for adaptation laws. The design of laws must (1) be responsive to change; (2) address equity dimensions of climate change; (3) implement innovative solutions; (4) maximize co‐benefits; and (5) establish processes for managing trade‐offs. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Abstract : Legal design principles for climate adaptation law. The design of laws for adaptations must (1) be responsive to change; (2) address equity dimensions of climate change; (3) implement innovative solutions; (4) maximize co‐benefits; and (5) establish processes for managing trade‐offs.